Autism spectrum disorder and the role of nuclear hormone receptors: insights and therapeutic implications - Chintalapally, Shivakanth; Rajanala, Kalpana; Upadhyay, Arun (Frontiers in Neuroscience, 2025)
Autism spectrum disorder is a neurological and developmental condition known to impact a person's learning, communication, and interpersonal interactions. Recent research has highlighted the role of nuclear hormone receptors (NHRs) in neurodevelopment and synaptic function, suggesting their potential involvement in ASD pathophysiology. NHRs regulate gene expression that are critical for neural differentiation, plasticity, and metabolic processes. Dysregulation of these receptors can lead to altered neural circuit formation and neurotransmitter imbalances, which are commonly observed in ASD. Understanding the interplay between NHRs and ASD could open new avenues for therapeutic interventions, providing hope for more personalized approaches to managing the disorder. One key receptor is retinoic acid-related orphan receptor-alpha (RORA), which was shown to be reduced in individuals with ASD. Among its numerous functions during development, RORA was shown to regulate the transcription of genes involved in neuronal differentiation, synaptic function, and neuroprotection. Studies have identified that RORA expression is reduced in individuals with ASD, particularly in the prefrontal cortex and cerebellum, affecting transcription of multiple ASD-associated genes. In the present review, we discuss the underlying mechanisms leading to ASD pathophysiology, various treatment modalities, the prospects of the RORA gene therapy approach, and future perspectives.